Bond stress-slip relationship in concrete-filled square stainless steel tubes. (4th April 2022) - Dai, Peng; Yang, Lu; Wang, Jie; Lin, Manfang; Fan, Junwei
Highlights: Push-out tests on fourteen CFSSST specimens were carried out. The effects of different factors on τ - S relationship were analysed and discussed. Based on the experimental results, an empirical τ-S relationship was proposed. Abstract: The application of stainless steel tubes in concrete-filled steel tube systems can significantly improve their corrosion resistance in comparison with those that employ carbon steel tubes. In this paper, a series of push-out tests were carried out to investigate the bond stress-slip behavior between stainless steel tubes and concrete. A total of 14 concrete-filled square stainless steel tube specimens were tested, covering two cross-sectional width-thickness ratios ( B / t = 30 and 50), two concrete strength ( f cu = 44 and 76 MPa), three rib stiffener types (ordinary, saw-shaped and perfobond leister) and two stainless steel grades (austenitic and duplex). The test results indicate that B / t, f cu and stainless steel grade have noticeable influences on the ultimate bond stress ( τ u ) in concrete-filled square stainless steel tube and the addition of rib stiffeners significantly improves the bond behavior. The bond mechanism at different stages of loading and the effect of various parameters on τ u are discussed. Based on the test results, an idealized bond stress-slip strain ( τ - εS ) curve was proposed, where good agreement between the test and the proposed model has been achieved.